Fiscal policy in a Real-Business-Cycle model with labor-intensive government services and endogenous public sector wages and hours - Aleksandar Vasilev (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Motivated by the high public employment, and the public wage premia observed in Europe, a Real-Business-Cycle model, calibrated to German data (1970-2007), is set up with a richer government spending side, and an endogenous private-public sector labor choice. To illustrate the effects of fiscal policy, two regimes are compared and contrasted to one another - exogenous vs. optimal (Ramsey) policy case. The main findings from the computational experiments performed in this paper are: (i) The op- timal steady-state capital tax rate is zero; (ii) A higher labor tax rate is needed in the Ramsey case to compensate for the loss in capital tax revenue; (iii) Under the optimal policy regime, public sector employment is lower, but government employees receive higher wages; (iv) The benevolent Ramsey planner provides the optimal amount of the public good, substitutes labor for capital in the input mix for public services produc- tion, and private output; (v) Government wage bill is smaller, while public investment is three times higher than in the exogenous policy case.
Keywords: E32; E62; H40; J5; 330; government spending; public employment and wages